PEMANFAATAN LINGKUNGAN SEBAGAI MEDIA BELAJAR DALAM PEMBELAJARAN DI TK NEGERI PEMBINA PONTIANAK SELATAN - Oczalina, Bella; Ali, Muhamad; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe environment is a real condition that includes the state of natural resources such as land, water, solar energy, minerals, and flora and fauna that grow on land and in the ocean. The environment can also be interpreted as a circle that surrounds human life and plays an important role , such as the existence of sun and water which are the necessities of human life. The purpose of this study was to describe the use of the environment as a learning media in learning at the TK of the Pembina Negeri Selatan Pontianak. With the subject of observation are the Kindergarten Teachers of South Pontianak State Trustees and kindergarten children of the Pembina Selatan District. From the results of the study, it was found that the use of the environment as a learning media in learning at the TK Pontianak Pembina Negeri Negeri uses lecture methods and demonstrations to explain to children. The teacher is expected to be able to help children with several techniques for using the environment to stimulate child development. Parents and teachers should communicate more frequently on a regular basis to help children grow up in interacting with others. The need for TK Trustees to add media related to child development.Â Keywords: beginning reading, early childhood, spelling method, institution word method.